Collaborative Guidance Practices in Ece: Parents and Teachers as Partners - Deri Hendriawan; Esya Anesty Mashudi; Nenden Sundari; Roby Naufal Arzaqi (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Parents’ and teachers’ collaboration is increasingly recognized as a cornerstone of effective early childhood education (ECE), particularly in the implementation of guidance practices that foster children’s holistic development. Guidance in ECE emphasizes understanding and supportive teaching rather than punitive discipline, positioning both teachers and parents as key facilitators of children’s growth. This study investigates how partnerships between parents and teachers are built and sustained within collaborative guidance programs in kindergartens using Epstein’s Framework of parental involvement. This qualitative study involved semi-structured interviews with teachers, parents, and principals from three kindergartens in Serang, Indonesia, and data were analyzed using Braun and Clarke’s thematic analysis. Findings reveal three key themes: (1) partnerships are grounded in mutual trust, structured communication, and shared responsibility; (2) collaborative guidance practices reflect several dimensions of parental involvement, with parenting and communicating emerging as the most dominant forms, particularly within personal-social guidance activities; and (3) challenges such as limited parental time, unequal participation, minimum training, and sociocultural hierarchy hinder sustained collaboration. The study contributes novel insight into how guidance services can be co-constructed by families and educators in ECE settings. Practically, the findings highlight the need for structured communication systems, capacity-building programs, and institutional support to strengthen parent–teacher partnerships in implementing guidance practices.